Pencatatan Perkawinan Lintas Kantor Urusan Agama di Kota Gorontalo: (Analisis Implementasi Surat Edaran Dirjen Bimas Islam Nomor: Dj.II.2/HM.01/942/2009) - Alinda Ahmad Ishak; Muhibbuddin Muhibbuddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
This paper aims to find out and analyze marital registration across the Office of Religious Affairs (KUA) in Gorontalo City by observing Circular Letter of the Directorate of Islamic Community Guidance Number: Dj.II.2 / 1 / HM.01 / 942/2009. This research is a descriptive-analytical field research. The approach used is a normative juridical approach with data collection methods in the form of observations, interviews and documentation studies. The results showed that 7 of 9 KUA in the City of Gorontalo, the Headman/Registrar of marriage did not know and read the Circular, while 2 of the 9 KUA in Gorontalo City who have read it are divided into two groups: First, assume that the purpose of the Circular applies only to normal marriages, not to apply to post-isbat marriages; Secondly, despite the contrary opinion, if faced with a real case in the field, Recording of post isbat marriage done by cross-KUA, will still receive and record it even if it is not in accordance with the contents of the circular and follow the court's ruling on the contents of the determination of the isbat. The author is of the opinion that the reality of cross-KUA marriages in Gorontalo does not go according to the rules contained in the Circular, and even seems to be ignored by the Headman/Registrar of marriage.